Ultra-high surface area mesoporous carbons for colossal pre combustion CO2 capture and storage as materials for hydrogen purification - Cox, Michael; Mokaya, Robert (Royal Society of Chemistry, 2017)
Carbon capture and storage (CCS) by solid adsorbents is currently attracting a great deal of attention. In this study, a new direction in the treatment of activateable carbon-containing precursors generated a family of mesoporous carbons that possess extremely high mesopore volume and hardly any microporosity. The mesoporous carbons, with up to 95% mesoporosity, have ultra-high surface area (2800 – 4000 m2g-1) and pore volume (2.5 – 3.6 cm3g-1). The porosity of the carbons, i.e., mesopores of size 25 - 50 Å and hardly any micropores, is favourable for CO2 uptake under conditions that are relevant to pre combustion CCS, i.e., 25 oC and pressure of 20 to 50 bar. The best performing carbons have near total absence of micropores; our findings suggest that the presence of microporosity is a limiting factor in the CO2 uptake capacity especially at high pressure (30 – 50 bar). The gravimetric (mmol g-1) CO2 uptake capacity of the mesoporous carbons is impressive; up to 28 (20 bar), 37 (30 bar), 46 (40 bar) and 55 (50 bar), which is equivalent to 2.42 g of CO2 per g of carbon. Furthermore, due to their packing density (0.25 – 0.4 g cm-3), the mesoporous carbons exhibit colossal volumetric CO2 uptake (in g l-1) of up to 480 (20 bar), 640 (30 bar), 780 (40 bar) and 930 (50 bar). The performance of the mesoporous carbons is such that, at 30 bar, they can hold more than 10 times the CO2 in a pressurized cylinder, and at 50 bar can store up to 470 cm3 cm-3. The all-round pre combustion CCS performance of the mesoporous carbons is significantly higher than that of the best carbons to date, and outperforms that of benchmark materials such as metal organic frameworks (MOFs). The carbons are highly suited, in terms of their CO2 adsorption capacity and CO2 selectivity over H2, as materials for hydrogen purification under syngas flow conditions.